CLASSROOM ASSESSMENT AND INTEGRATED-LEARNING MODEL ON SOCIAL SCIENCE - AHMAD, AHMAD; SASTRAWIJAYA, YULIATRI (Jurnal Evaluasi Pendidikan, 2011)
This study is aimed at finding the effect of classroom assessment and in integrated learning learning model towards the students learning achievement on social science subject matter, the sample consisted of 92 junior high school students are taken with a multi-state random sampling with a 2 x 2 factorial design. Data using Analysis of Variance followed by Tukey test. The research reveals the following conclusion: (1) the students’ learning achievements of social science treated with project assessment is higher than that of portfolios assessment, (2) the students’ learning achievements of social science treated with webbed model is higher than that of connected model (3) there is a significant interaction between classroom assessment from integrated learning model towards the students’ of social science learning achievements, (4) the group of social science students measured with project assessment, their learning achievement is higher than that of the students’ treated with connected learning model, (5) the group of social science students’ measured with portfolios, the students’ learning achievement treated with webbed model is lower than that of the learning achievements of the students treated with the connected learning model, (6) the group of social science students treated with webbed model of learning, the students’ learning achievement measured with project assessment is higher than that of the students’ learning achievements measured with the portfolios assessment, and (7) the group of social science students treated with connected model of learning, the students’ of social science learning achievement measured with project assessment is lower than that of the students’ learning achievements measured with the portfolios assessment. Based on the result of the research it’s expected that the social science teachers in teaching and learning process in order to apply webbed model and project assessment.